ПЕРИФЕРИЧЕСКАЯ ВЕГЕТАТИВНАЯ НЕДОСТАТОЧНОСТЬ. КЛИНИЧЕСКИЙ СЛУЧАЙ - Л. М. Фархутдинова; Е. В. Первушина; В. М. Садыров; П. С. Гусева; Н. И. Квезерели; Г. А. Биглова; Н. В. Калашченко (SINAPS LLC, 2014)
The article contains a description of a clinical case of refractory hypotension, developed after surgery for pituitary macroadenoma. Postoperative period was complicated by the development of acute myocardial infarction, connected with aggravation of megakariocyte leukemia. Presented differential diagnosis causes hypotension in a patient with severe comorbidity.